A review: The use of mangrove for biomonitoring on aquatic environment. Issue 1 (December 2020) - Wilda, R; Hamdan, A M; Rahmi, R
Abstract: Mangroves have been investigated widely as plants that can absorb and accumulate heavy metals in their tissues. Due to that ability, mangroves have been used to reduce heavy metals in the aquatic environment. Furthermore, mangroves have been used for biomonitoring of heavy metals pollution. The use of mangroves for biomonitoring on aquatic environments has been considered as a cheap, rapid, and sufficient method. The mangrove is an organism that has the ability to absorb the contaminants of heavy metal and to function as fine pollutants trap. However, to develop this technique for wide use, research and investigation are still needed. This paper is aimed to describe the future direction of mangrove studies of using mangroves as a biomonitoring agent. Based on the review, Rhizophopora mucronata and Avicennia marina are mangrove species that have a promising ability to be used for biomonitoring in the aquatic environment.